Há possibilidade do ensino da história desenvolver o pensamento teórico? - Marques, Antonia Batista (2009)
The expectation that there is a relationship between the teaching of history and the development of theoretical thinking , this study aimed to examine this relationship with the collaboration of two teachers who teach in the fourth year of elementary school in a public school in the city of Mossley - RN . Sues the theoretical and methodological contributions are identified with the history Dialectical Materialism . The methodological approach was collaborative research . Was based on studies of Vygotsky ( 1998, 2001 ) , Rubinstein (1965 , 1973) , Ibiapina (2007 , 2008) , Afanassiev (1985 ) , Goes (2003 ) , Ferreira and Ibiapina (2005 , 2006, 2007 ) , Davydov (1981 ) , Glenisson (1991 ) among others . The methodological procedures consisted of : meetings , questionnaire , interview , cycles of reflective studies , reports of experiences and reflective session. For data analysis , we used the methodology of conceptual elaboration , proposed by Ferreira (2009 ) and the shares of reflection proposed by Magalhães (2000 ) . Data analysis indicates the predominance of empirical thinking of collaborating both with regard to the process of design and ( re ) development of the concepts of history and theoretical thinking on the relationship between history teaching and the development of theoretical thought . However , we see the beginning of the start of the change process in thinking the teaching of history